HOW HALAL TRANSPORTATION SYSTEM IMPACT THE LOCATION ROUTING PROBLEM - Oki Anita Candra Dewi; Luki Trihardani (Badan Penerbit Jurnal, Faculty of Engineering, Universitas Brawijaya, 2017)
Halal products become more popular in the world market today that increase the demand of other halal services especially in halal distribution system. These services are designed not only for profitability but its ability to serve customers to maintain the integrity of their halal products. The important decision of designing halal distribution system is determining the location of facilities. In this paper, a halal and non-halal demand constrains with vehicle flow formulation of an uncapacitated location routing model is presented. Halal and non-halal goods are not mixed on a same transportation vehicle. Its a clear difference in transportation of halal and non-halal goods. A location routing problem used to minimize total cost simultaneously. A heuristic algorithm is developed to solve minimum cost considering halal aspect. This paper conduct some numerical experiments to show the behavior of this algorithm.